Questioning the assumptions, sustainability and ethics of endless economic growth - Haydn Washington (Journal of Risk and Financial Management, 2021)
This article questions the assumptions, sustainability and ethics of endless economic growth on the basis of environmental science, ecological economics and ecological ethics. It considers the impossibility and unsustainability of endless physical growth on a finite planet. It considers the indicators of environmental degradation (all increasing) and argues that society's addiction to endless growth is irresponsible. It discusses the key problem of denial, and how this blocks us from finding workable solutions. It discusses how in theory GDP could continue to grow modestly in the future if we adopted a steady-state economy where growth was not caused by an expanding population or resource use. However, this model is currently unpopular, with many advocating the green and circular economies that are partial solutions, and which justify ongoing growth through a fantasy of absolute decoupling. I discuss the need for society to change its anthropocentric worldview to one of ecocentrism. I then question whether the UN Sustainable Development Goals are actually ecologically sustainable. I discuss how, when we ignore the problems of an endlessly growing economy, we create significant risk to society. Rather than a focus only on 'sustainable economic growth', I suggest it is time to focus centrally on an ecologically sustainable economy and future.
Keywords: 330; economic growth; steady-state economy; ecological economics; denial; ecocentrism; anthropocentrism; ecological ethics; decoupling; Sustainable Development Goals; ecological sustainability